Kurikulum Pendidikan Agama Islam Pada Era Revolusi Industri 4.0 - Mustiliani Mustiliani; Rahma Safitri; Sulis Mariyati (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
The Industrial Revolution 4.0 has significantly transformed the educational system, including Islamic Religious Education (IRE), through the integration of digital technology into the learning process. While this transformation offers opportunities to improve learning quality, it also presents challenges such as moral degradation, inadequate ethical digital literacy, and the weakening of students' religious character. This study aims to analyze the development of the Islamic Religious Education curriculum in the Industrial Revolution 4.0 era by integrating religious values into digital learning based on the perspective of Ismail Raji Al-Faruqi and strengthening character and moral education based on the educational philosophy of Imam Al-Ghazali. This research employed a library research method with a qualitative descriptive approach by analyzing and synthesizing ten relevant journal articles. The data were examined using content analysis through comparison, categorization, and interpretation based on the theoretical frameworks adopted in this study. The findings indicate that the Islamic Religious Education curriculum in the Industrial Revolution 4.0 era should systematically integrate digital technology with the values of tawhid, morality, and Islamic ethics. Ismail Raji Al-Faruqi's perspective emphasizes the Islamization of knowledge by integrating modern sciences with Islamic values, while Imam Al-Ghazali highlights the importance of tazkiyatun nafs (self-purification), exemplary conduct, habituation of righteous deeds, and the balance between knowledge and practice as the foundation of education. Therefore, the development of the Islamic Religious Education curriculum should produce learners who possess digital competence, strong religious character, noble morality, and the ability to utilize technology wisely in accordance with Islamic values.